Analisis Determinan Perilaku Pencegahan Penularan Tuberkulosis: Studi Berbasis Teori Preceded-Proceed di Wilayah Urban Kota Makassar - Andi Magfirah Hamsi; Kartini; Ivan Wijaya; Ariani (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Tuberculosis (TB) remains a global health problem. Indonesia ranks second highest in the world in terms of TB cases, accounting for 10% of the total with an estimated 1,092,000 cases. The transmission of TB is greatly influenced by the behavior of patients in taking measures to prevent TB transmission. This is due to the lack of behavior of patients in preventing transmission. The purpose of this study was to determine the factors associated with patient behavior in efforts to prevent TB transmission at the Cendrawasih Community Health Center in Makassar City. This study used a quantitative method with an analytical observational approach and a cross-sectional study design. There were 94 TB patients at the Cendrawasih Community Health Center who participated in the study. Purposive sampling was used to select the sample, and a questionnaire was used as the research instrument. Data analysis was performed using the chi-square test with IBM SPSS version 25. The results showed that there was a significant relationship between knowledge (p=0.004), smoking habits (0.046), family support (p=0.018), and availability of a private bed (p=0.000) with TB transmission prevention behavior among TB patients. Multivariate analysis results showed that family support was the most influential variable on TB transmission prevention behavior in the urban area of Makassar City (p=0.001; OR 0.195; 95% CI: 0.075-0.509). From the research results, it can be concluded that the family support variable is the most dominant factor influencing TB transmission prevention behavior in the urban area of Makassar City